Do students in different courses of study think the same way in complex problem solving? [Poster presentation] - Wu, H.; Molnár, G. (20th biennial conference of the European Association for Research on Learning and Instruction (EARLI 2023), 2023)

在教育中促進無偏見和可靠的人工智能:賦能學生認知能力 [Presentation] - Wu, H. (第一屆人工智能教育應用論壇, 2023)

Impacts of Policies and Infrastructure on the Usage of Electric Vehicles in Macao - Weng Chi Lei; Tai, On Teng (2023 Symposium on Environmental Science and Sustainable Technology (ESST2023), 2023)

Towards a framework of teacher professional development: The case of early literacy education in Macau - Tse, T. P. M.; Mak, M. C. K; Chu, K. W.; Cheng, P. W.; Ho, G. W. S.; Chan, A. O. K; Ng, M. H.; Leong, K. I. Q. (The 6th Annual Conference for the Association for Reading and Writing in Asia (ARWA 2022), 2022)

An Action Research on Supporting Children's Chinese Literacy Learning by Using Visualization Method - Tong, M. K.; Sun, C. R. (7th International Conference on Teaching Chinese Second Language, 2022)

Comparing Urban Rules for Urbanizing Villages in Hong Kong, Macau, and Shenzhen - Tieben, H.; Chu, J.; Soares, Nuno (ISUF 21st International Seminar of Urban, 2014)

澳門品德與公民教育校本課程初探 - Tchiang, I.; Ge, Yun (2nd Summit of Youth Education and Development in Hong Kong and Macau, 2020)

Mangroves as a nature-based solution for a cleaner and safer Macao - Tagulao, Karen (Guangdong-Hong Kong-Macao Greater Bay Area Marine Sustainable Development Seminar, 2022)

Mangroves for phytoremediation of coastal water eutrophication in Macao, SAR China - Tagulao, Karen (The 9th WETPOL (Wetland Pollution and Dynamics), 2021)

A Small Action Research of Using Flipped Classroom Approach to Supporting Diversity Students’ Learning in University. - Sun, C. R. (International Conference on Learning and Teaching, 2021)

Kindergarten Teachers' Attitudes towards Inclusive Education: Perspectives from Macau. - Sun, C. R. (21st PECERA International Conference, 2021)

A experiência de Macau e Hong Kong – Ensino de Arquitectura entre o Local e o Global - Soares, Nuno (VI Congresso Internacional do Conhecimento Científico ISECENSA, 2018)

ASIA URBAN LAB – Comparative Studio - Soares, Nuno (DATUM: EDU International Education Conference 2018, 2018)

Cross Border Lab: Reframing the Urban Edge - Macau x Zhuhai - Soares, Nuno (Manipal International Symposium on Design, 2020)

Local Matters - Design Driven by Urban Conditions [Video] - Soares, Nuno (TEDx Senado Square. TED Conferences., 2020)

Pavilhão de Bambu Intertwine – Preservação, Inovação e Promoção do Património Imaterial de Macau - Soares, Nuno (VIII Fórum Internacional CIALP, 2022)

Public Matters: Identity, Design, and Placemaking in Macau’s Inner Harbou - Soares, Nuno (Making Place in the Greater Bay Area International Symposium, 2021)

Reframing the Urban Edge - Design Strategies for Macau x Zhuhai Waterfront - Soares, Nuno (The Greater Bay Area Urban Design Conference, 2020)

SHAPED BY USE - Individual designs reshaping the city - Soares, Nuno (HKIA Cross-Strait Architectural Design Symposium and Awards 2017, 2017)
Macau is the most densely populated territory in the world, a small but complex urban landscape populated by a myriad of informal devices that produce a dramatic impact on the image and use of the city, creating an ever-present layer shaped by use. The traditional fields of architectural and urban morphology base their analysis on the private and public space, on the forms of buildings, block, streets, and squares. However, the urban landscape is not only shaped top down by market forces, governments, institutional players, but also bottom-up by thousands of small scale interventions carried out daily by their inhabitants, to solve problems or seize opportunities, on the normal process of usage. This research summarizes an extensive analysis of Macau’s urban landscape focused on this layer of appropriation, aimed to identify these shapes generated by use or, in other words, the devices that materialize the phenomenon of appropriation of the public space. They can take the shape of window cages, rooftop houses, canopies, annexes, hawker booths, and outdoor ads. SHAPED BY USE Individual designs reshaping the city – is a typo morphological essay aimed to provide a methodological tool for the analysis of such phenomena, both in this and other similar urban contexts as well as a compelling starting point to speculate on how small scale individual designs can contribute to reactivate and be harnessed to positively reshape the city.

SHAPED BY USE - Mapping, Debating and Envisioning the Customization of Urban Space - Soares, Nuno (AIA (American Institute of Architects) Japan CES Lecture Series, 2018)

Macau's First Modern University: Exploring the Early History of the University of East Asia - Roberts, Priscilla (2023)

Tracing Modern Macau’s Evolving Global Role Views from Transnational Archives - Roberts, Priscilla (Third Annual Conference of Macao Studies, 2023)

Monitor or On-site? Macau kindergartener parents’ learning experience in face-to-face and online parent education seminars - Ng, M. H.; Leong, K. I. Q.; Mak, M. C. K.; Cheng, P. W.; Ho, G. W. S; Chan, A. O. K.; Tse, T. P. M. (The International Conference on Learning and Teaching 2021 (ICLT 2021), 2021)

Automatic Classification System for Subjects Exposed to Short-Term Stress Based on Facial Expression Analysis and ElectroDermal Activity - Motta, P.; Silva, B.; Furtado, F.; Lobo Marques, J. A. (XXVIII Brazilian Congress of Biomedical Engineering CBEB 2022, 2022)

From ‘Mixed Methods’ to ‘Integration’ in Social Science Research - Morrison, Keith (Symposium European Scientific Institute, 2023)

Life Is not a Walk across a Field - Morrison, Keith (European Scientific Institute, 2024)

The local contemporary art of Macao in a state of ambivalence - Mendes, Carla de Utra; Simões, José Manuel (Behind the Façade: Interdisciplinary perspectives on Macao, 2014)

The other side of creative industries in Hong Kong and Macau - Mendes, Carla de Utra; Simoes, José Manuel (2014 International Conference of Culture and Creativity (ICCC 2014), 2014)

Cyberculture and Multimodal Digital Games in Learning Environments: Fostering Creativity in Macau’s Educational System - Martins de Abreu, F.; Barbosa, Alvaro (LISBON CONSORTIUM - VIII Lisbon Summer School for the Study of Culture “Cyber+Cipher+Culture", 2018)

The impact of multimodal digital games in children’s learning environments - Martins de Abreu, F.; Barbosa, Alvaro (MRI INTERNATIONAL CONFERENCE - Common Good and Education, 2017)

Connecting Neuromarketing and AI - a path to new insights and analysis - Marques, J. A. L. (Neuromarathon, 2023)

Developing Neuromarketing Innovative Research - Lobo Marques, J. A. (Neuromarathon 2022, 2022)

Finding the “BUY BUTTON”. The creation of the Laboratory of Neuroeconomics at USJ - Lobo Marques, J. A. (12th International Conference on E-business, Management and Economics (ICEME 2021))

Intelligent Data Fusion System for Assessing and Classifying the Long-Term Effects of Exposure to COVID-19 in Pregnancy (Long Covid): Associated Neurophysiological and Epigenetic Mechanisms and Consequences for Infant Development - Lobo Marques, J. A. (2023 7th International Conference on Data Mining, Communications and Information Technology (DMCIT & CSMO 2023), 2023)

IoT-based smart health system for ambulatory maternal and fetal monitoring - Lobo Marques, J. A. (Symposium on Intelligent Manufacturing and Artificial Intelligence Technologies (ISIMAIT 2022), 2022)

Neuroeconomics Applications Based on Multiple Monitoring Tools. - Lobo Marques, J. A. (13th International Conference on E-business, Management and Economics (ICEME 2022), 2022)

The Vital Signs of Roman Catholic Liturgical Music among the Cantonese-Portuguese-English Speaking Communities in Macau 羅馬天主教禮儀聖樂在澳門粵葡英三語群體間之生命力’ - Law, Cyril Jerome (2019)

澳門天主教教理培育委員會《天主教教理》卷二「基督奧跡的慶典」課程 - Law, Cyril Jerome (2019)

「紐曼樞機：兩心對話，一生皈依」澳門紐曼樞機藝文館開幕活動系列專題講座 （Special Lecture on Cardinal Newman for the Opening of the Centro de Cultura e Artes Performartivas Cardeal Newman de Macau） - Law, Cyril Jerome (2020)

「道」與「導」：與聖紐曼樞機反思生命中皈依與教學之使命 Leading the Way - Reflecting on the Mission of Learning and Conversion of Life with St John Henry Newman (1801-1890) - Law, Cyril Jerome (2021)

馬相伯研究的點線面 – 生命、史料、信仰(On Ma Xiangbo Studies) - Law, Cyril Jerome (2019)

Career Planning of Doctoral Students in Macau: Linking Individual Experience to Macro Picture - Ge, Yun (VHERA Symposium, 2022)

The Role of University in High-Level Human Capital Cultivation in China’s West Greater Bay Area - Ge, Yun (ICHE XVI International Conference on Higher Education, 2022)

Understanding Chinese Model of Government-University-Industry Collaborations in Research and Education: The Case of Macau SAR. - Ge, Yun (IFCU’s International Centre for Research and Decision Support’s Research Talk series, 2023)
Higher Education in Macau has been benefiting from a multi-layered institutional environment under China’s One-Country-Two-Systems. This presentation introduces research and education policies and practices of Macau universities under China’s national plan of the Greater Bay Area development. It aims to demonstrate and analyze how higher education actors collaborate with local and regional governments and industrial sectors in human capital formation and research innovations.

澳門教師文化回應教學認知與實踐研究 - Ge, Yun (3rd Summit of Youth Education and Development in Hong Kong and Macau, 2021)

澳門課程改革與發展: 政策與實務 - Ge, Yun (4th Summit of Youth Education and Development in Hong Kong and Macau, 2022)

澳門特殊與融合教育的發展及教師培訓 - Ge, Rochelle Yun (知行合一特殊教育高質量發展國際研討會, 2023)

課程變革的趨勢和具澳門特色的課程發展 - Ge, Rochelle Yun (Curriculum and Teaching in a Global Perspective: Reforms, Opportunities and Challenges Symposium, 2023)

AI-based Multimodal Qualitative Mapping of Macao Soundscape - Estadieu, G; Cheung, Y.Y. (United Nations World Data Forum, 2023)

SOUNDSCAPE.AI - A Sonic Perspectives on Macau - Estadieu, G (Iberian Soundscapes Conference, 2023)

Contemplation and Leadership: In the Footsteps of Fr. Yves Raguin, S.J. - Duraj, Jarosław (Macau Ricci Institute Public Forum, 2021)

Fr. Yves Raguin, S.J. and Interreligious Dialogue - Duraj, Jaroslaw (Macau Ricci Institute Public Forum, 2023)

Developing programs for preschool children to enhance Chinese literacy: A Macau-based example - Chu, K. W.; Mak, M. C. K; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S.; Ng, M. H.; Ng, S. K. (The 7th Annual Conference for the Association for Reading and Writing in Asia (ARWA 2023), 2023)

Developing programs for preschool children to enhance Chinese literacy: A Macau-based example. - Chu, K. W.; Mak, M. C. K.; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S; Ng, M. H. (The 7th Annual Conference for the Association for Reading and Writing in Asia (ARWA 2023), 2023)

Reciprocity in a school-university partnership project: Towards a Macau-based Give-Get Model - Chu, K. W.; Mak, M. C. K.; Ng, M. H.; Wong, U. W. K.; Cheng, P. W.; Tse, T. P. M.; Ho, G. W. S (The IV Uniservitate Global Symposium 2023, 2023)

The concept of “Object-image” revisited through the interactive-film installation “Sense of Place - Caires, C. S; Estadieu, G (Besides the Screen, 2020)

ARQUITECTOS ANÓNIMOS: a Sample of a Generation [Keynote Speak] - Afonso, Filipe (Public Lecture of Faculty of Creative Industries, University of Saint Joseph, 2019)

CRISIS BREEDS CREATIVITY - Afonso, Filipe (Chinese University Of Hong Kong - Making Place in the Greater Bay Area, International Symposium, 2021)

Post Disaster Temporary Housing System based on Generative Design Method - Afonso, Filipe (The 6th International Conference on Architecture, Materials and Construction ICAMC, 2020)

Potential for the design of an energy saving facade system using agglomerated cork: implications in subtropical climates - Afonso, Filipe (The 2nd International Conference on Sustainable Buildings and Structures, 2019)

Study of the Compositional Rules of Design in Chaoshan Traditional House: A Computational Approach - Afonso, Filipe (ARTECH 2021: 10th International Conference on Digital and Interactive Art, 2021)